Status of Supply Chain Management in Organized Vs Unorganized Retail - Singh, Nityanand (Indian Journal of Marketing, 2010)
The Indian retail sector is highly fragmented with 97% of its business being run by the unorganized retailers like the traditional family run stores and corner stores. The 3% share of organized retail is quite low when compared even to the other emerging countries. The organized retail, however, is at a very nascent stage, though attempts are being made to increase its proportion to 9-10% by the year 2010, bringing in a huge opportunity for prospective new players. The sector is the largest source of employment after agriculture, and has deep penetration into rural India; generating more than 10% of India’s GDP.